Analysis of simulated dilute anode tail-gas combustion characteristics on a CFR engine - Balu, Alexander, author; Olsen, Daniel, advisor; Windom, Bret, committee member; Baker, Daniel, committee member (Colorado State University. Libraries, 2020)
Recent innovations in metal-supported solid oxide fuel cells (MS-SOFC) have increased the longevity and reliability of fuel cells. These innovations drive the desire to create power generating systems that combine different ways of extracting power from a fuel to increase overall fuel conversion efficiency. This investigation assesses the feasibility of operating an internal combustion engine (ICE) with the anode tail-gas, which is a blend of H2, CO, CO2, H2O, and CH4, exhausted by a metal-supported solid oxide fuel cell (MS-SOFC). This engine would be used to support the fuel cell balance of plant equipment, including a compressor and expander, and produce excess electrical power. Seven variations of the expected anode tail-gas blends were determined by varying the dewpoint temperature of the fuel. In three of the test blends, CO2 replaced the water content of the fuel to allow for initial feasibility testing without the capital investment required to simulate the tail-gas with steam injection. Gas blends are tested by combining separate flows of each constituent, and combustion is tested using a Cooperative Fuel Research (CFR) engine. Compression ratio (CR), spark timing, intake manifold temperature (IMT), and boost pressure were manipulated to obtain optimal operating conditions. All test blends produced power and reached stable engine operation. Response surface method (RSM) optimization was used to experimentally optimize operating parameters and determine the maximum achievable efficiency utilizing the CFR engine. Initial feasibility testing performed on test blends with CO2 in place of water showed that all combinations successfully produced power in the engine. The mixture with the highest levels of CO2 was problematic and required an increased CR of 14.4:1, advanced timing of 40° before top dead center (BTDC), and an increased IMT of 70℃. All CO2 test blends operated at brake efficiencies ranging from 12-17% during initial testing. After the feasibility of this project was determined, a steam generator and steam flow meter were installed and used to fully simulate the anode tail-gas blends with steam injection. All fully simulated anode tail-gas blends produced power in the engine, although the blend with the most water content caused operational problems with the CFR engine test stand. These problems were caused by large amounts of water entering the engine lube oil system. RSM optimization was performed on the most viable test blends which had steam injection to 40℃ and 90℃ fuel dewpoint temperatures. During optimization, the 40℃ and 90℃ dewpoint temperature blend brake efficiency increased from 20% to 22.2%, and 17% to 22.3%, respectively. This study determined that ICE operation on dilute anode tail-gas is possible. Anode tail-gas combustion data was collected and used to inform engine and combustion models to facilitate prototype engine development for further testing.
Keywords: CFR; dilute; solid oxide fuel cell; combustion; anode tail-gas; engine